Pendidikan Humanisme Religius: Telaah Model Pendidikan Pondok Pesantren Syafi’i Akrom Kota Pekalongan - Tri Puji Agustina (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
Pesantren is a basic for the development of human values. Education in pesantren pay attention to aspects of human potential as well as religious social beings, as well as individuals who have the potential to unleash capacities. This study sought to uncover implementation education in Pesantren Sya'fii Akrom Pekalongan whose perspective is religious humanism. The field research revealed that the process of learning between teachers and students occurs with intense interaction patterns that uphold human values and religion, so that education in pesantren Shafii Akrom is called religious humanism education. This can be seen in the well-built humanitarian values. The mutual respect, patience, diligence, discipline and values ​​of tolerance developed become the main indicators of education based on the values ​​of religious humanism.